Methods of selection of soybean genotypes for tolerance to rain on pre-harvest (Research, Society and Development, 2022)
Soybean production chain is facing serious challenges for high quality seed and grain production. This paper proposes a simple method to select genotypes with tolerance to excess moisture. The study was divided into three stages. Stage I consisted in plant production and standardization of maturity for 25 seeding genotypes in Passo Fundo-RS during 2013-2014 growing season 500 plants were harvested from each genotype at R7-R8 stage. Stage II was composed by rainfall and temperature simulation assays which were carried out in greenhouse facility of Cambé-PR. Stage III consisted of physiological seed quality determination. Samples were evaluated for 1000-seeds weight, germination, first count of germination, accelerated aging and shoot and root dry matter. Simulation of rain for three days during preharvest period resulted in reduced seed viability and vigor in genotypes DMARIO59i, A4725RG, NS4823 and FPS URANO RR indicating consideration of the harvesting time close to R8 stage for high quality seed production in these genotypes.